Delayed presentation of HIV among older individuals: a growing problem. Issue 4 (April 2022) - Justice, Amy C; Goetz, Matthew B; Stewart, Cameron N; Hogan, Brenna C; Humes, Elizabeth; Luz, Paula M; Castilho, Jessica L; Nash, Denis; Brazier, Ellen; Musick, Beverly; Yiannoutsos, Constantin; Malateste, Karen; et al.
Summary: Late presentation for care is a major impediment to the prevention and effective treatment of HIV infection. Older individuals are at increased risk of late presentation, represent a growing proportion of people with late presentation, and might require interventions tailored to their age group. We provide a summary of the literature published globally between 2016–21 (reporting data from 1984–2018) and quantify the association of age with delayed presentation. Using the most common definitions of late presentation and older age from these earlier studies, we update this work with data from the International Epidemiology Databases to Evaluate AIDS (IeDEA) consortium, focusing on data from 2000–19, encompassing four continents. Finally, we consider how late presentation among older individuals might be more effectively addressed as electronic medical records become widely adopted.